Selective axonal growth of embryonic hippocampal neurons according to topographic features of various sizes and shapes - Christine E Schmidt (Dove Medical Press, 2010)
David Y Fozdar1*, Jae Y Lee2*, Christine E Schmidt2–6, Shaochen Chen1,3–5,7,1Departments of Mechanical Engineering, 2Chemical Engineering, 3Biomedical Engineering; 4Center for Nano Molecular Science and Technology; 5Texas Materials Institute; 6Institute of Neuroscience; 7Microelectronics Research Center, The University of Texas at Austin, Austin, TX, USA *Contributed equally to this workPurpose: Understanding how surface features influence the establishment and outgrowth of the axon of developing neurons at the single cell level may aid in designing implantable scaffolds for the regeneration of damaged nerves. Past studies have shown that micropatterned ridge-groove structures not only instigate axon polarization, alignment, and extension, but are also preferred over smooth surfaces and even neurotrophic ligands.Methods: Here, we performed axonal-outgrowth competition assays using a proprietary four-quadrant topography grid to determine the capacity of various micropatterned topographies to act as stimuli sequestering axon extension. Each topography in the grid consisted of an array of microscale (approximately 2 µm) or submicroscale (approximately 300 nm) holes or lines with variable dimensions. Individual rat embryonic hippocampal cells were positioned either between two juxtaposing topographies or at the borders of individual topographies juxtaposing unpatterned smooth surface, cultured for 24 hours, and analyzed with respect to axonal selection using conventional imaging techniques.Results: Topography was found to influence axon formation and extension relative to smooth surface, and the distance of neurons relative to topography was found to impact whether the topography could serve as an effective cue. Neurons were also found to prefer submicroscale over microscale features and holes over lines for a given feature size.Conclusion: The results suggest that implementing physical cues of various shapes and sizes on nerve guidance conduits and other advanced biomaterial scaffolds could help stimulate axon regeneration.Keywords: axon guidance, micropatterning, polarization, surface topography, tissue engineering